2009
DOI: 10.1073/pnas.0807136106
|View full text |Cite
|
Sign up to set email alerts
|

MLL5, a trithorax homolog, indirectly regulates H3K4 methylation, represses cyclin A2 expression, and promotes myogenic differentiation

Abstract: Most cells in adult tissues are nondividing. In skeletal muscle, differentiated myofibers have exited the cell cycle permanently, whereas satellite stem cells withdraw transiently, returning to active proliferation to repair damaged myofibers. We have examined the epigenetic mechanisms operating in conditional quiescence by analyzing the function of a predicted chromatin regulator mixed lineage leukemia 5 (MLL5) in a culture model of reversible arrest. MLL5 is induced in quiescent myoblasts and regulates both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
127
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 40 publications
4
127
0
4
Order By: Relevance
“…In this context, it is noteworthy that the myeloid/lymphoid or mixed-lineage leukemia 5 gene (MLL5), a trithorax homolog with a crucial role in adult hematopoiesis and a postulated role in chromatin remodeling and in the control of cellular growth, was recently mapped to 7q22, a region that is frequently deleted in AML [54][55][56][57] .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is noteworthy that the myeloid/lymphoid or mixed-lineage leukemia 5 gene (MLL5), a trithorax homolog with a crucial role in adult hematopoiesis and a postulated role in chromatin remodeling and in the control of cellular growth, was recently mapped to 7q22, a region that is frequently deleted in AML [54][55][56][57] .…”
Section: Discussionmentioning
confidence: 99%
“…However, such downregulation might not be directly related to the inhibition of Top1, as b-lapachone, another class of Top1 inhibitor with a mode of action distinct from CPT, was unable to degrade MLL5 or activate p53 through Ser392 phosphorylation (Supplementary Figure S9). RNAi-mediated knockdown of MLL5 was previously shown to delay or arrest the G 1 /S transition (Cheng et al, 2008;Sebastian et al, 2009). Therefore, it is plausible that the elimination of MLL5 is required for delaying the cell cycle progression, allowing deployment of damage repair mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopically overexpressed MLL5 caused cell cycle arrest at G 1 /S phase (Deng et al, 2004), whereas siRNA-mediated knockdown of MLL5 arrested cell cycle at both G 1 /S and G 2 /M phases (Cheng et al, 2008). Upon MLL5 knockdown, the entry of quiescent myoblasts into S-phase was delayed, but the completion of S-phase progression was hastened (Sebastian et al, 2009). Recently, we showed that phosphorylation of MLL5 by mitotic kinase Cdc2 is required for mitotic entry (Liu et al, 2010b).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Whether MLL5 possesses the histone lysine methyltransferase activity is still highly debatable. Several reports suggested that MLL5 lacks such intrinsic methyltransferase activity (14,25). However, a short N-terminal isoform of MLL5 that contains both the PHD and SET domain was recently identified in a multisubunit complex in association with nuclear retinoic acid receptor-␣ (26), in which the isoform acts as a mono-and dimethyltransferase to H3K4.…”
mentioning
confidence: 99%